11x-15=6x

Simple and best practice solution for 11x-15=6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x-15=6x equation:


Simplifying
11x + -15 = 6x

Reorder the terms:
-15 + 11x = 6x

Solving
-15 + 11x = 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-15 + 11x + -6x = 6x + -6x

Combine like terms: 11x + -6x = 5x
-15 + 5x = 6x + -6x

Combine like terms: 6x + -6x = 0
-15 + 5x = 0

Add '15' to each side of the equation.
-15 + 15 + 5x = 0 + 15

Combine like terms: -15 + 15 = 0
0 + 5x = 0 + 15
5x = 0 + 15

Combine like terms: 0 + 15 = 15
5x = 15

Divide each side by '5'.
x = 3

Simplifying
x = 3

See similar equations:

| -10x-4(3x-2)= | | -15+32=x | | y+32=17 | | (6x-1)-(3x-5)= | | n-13*3=12 | | 3t/7=14 | | X^2-2=x/6 | | 6x-59=4x+-9 | | (4m^3-3m^2+5)-(3m^3+m^2-3)= | | 2*3.14*r=7.09 | | 8n=12 | | x^2+8x+15=33 | | 1/3(12x-15) | | 20=2d+6 | | 4x-28/3=3x+21/4 | | n(n+1)(n-2)(n+4)=84 | | 8x+5x=143 | | 2x^2+x+0=0 | | 3x-5=10-47 | | -2+9=21 | | 4x-28/3 | | 1.75x+1.00=13.75 | | 7x+26=3x+74 | | 5y^2+5x+10y+1=0 | | -5k-4=-19 | | 11-7x=71-21x | | 2.5x^2+8.5x=0 | | 25x^2+85x=0 | | 2x-10y=-10 | | 7(x-5)=7x-35 | | 6(x+3)=9-2[x-4(x+1)] | | h=235t-16t^2 |

Equations solver categories